Psychological Vulnerability and Hope as Serial Mediators in the Association between Psychological Maltreatment and Romantic Relationship Satisfaction - Kutuk, Hasan (SPRINGER, 2025)
This study aims to examine the serial mediating roles of psychological vulnerability and hope in explaining the impact of childhood psychological maltreatment on romantic relationship satisfaction in adulthood. The research was conducted with the participation of 401 young adults, and data were collected through self-report instruments. The proposed theoretical model was tested using structural equation modeling. The findings indicate that psychological maltreatment negatively affects romantic relationship satisfaction both directly and indirectly through psychological vulnerability and hope. Notably, psychological vulnerability and hope function as partial serial mediators in this relationship. The results suggest that childhood psychological maltreatment may undermine individuals' internal psychological resources, thereby reducing their capacity to experience satisfaction in romantic relationships during adulthood. In this context, early psychological interventions and hope-based counseling practices may offer promising directions for therapeutic efforts aiming to enhance relational well-being among individuals exposed to psychological maltreatment.
Keywords: Psychological Maltreatment; Psychological Vulnerability; Hope; Romantic Relationship Satisfaction; Serial Mediation; CHILD MALTREATMENT; MARITAL SATISFACTION; QUALITY; VALIDATION; HISTORY; COUPLES; ABUSE; Psychiatry